Effects of timolol maleate, levobunolol and apraclonidine on intraocular pressure, pupil size, blood pressure and heart rate in beagles (2023)
The aim of this study was to evaluate changes in intraocular pressure (IOP), pupil size (PS), blood pressure (BP), heart rate (HR), and ECG variables (Pms wave PmV, PR interval, QRS complex, RMV wave and QT intervals) over time during the instillation of 0.5% timolol, 0.5% levobunolol and 0.5% apraclonidine in clinically normal dogs. Ten adult beagles were used. Baseline values were measured at 8a.m., 2p.m. and 8p.m., for three consecutive days. A waiting period of 10 days between the administrations of each drug was established. For 15 consecutive days, the drug being tested was instilled in one eye of each dog twice a day (7a.m. and 7p.m.). The parameters were evaluated at the aforementioned times on days 3, 6, 9, 12 and 15. Data were statistically compared using the Bonferroni test and one-way repeated measures analysis of variance (P<0.05). The Pearson test was used to evaluate any correlation between QT interval, HR and BP. The tested drugs did not find a decrease in IOP. A significant decreased in PS was observed in almost all dogs following levobunolol administration, relative to the control eye. A significant decrease in HR was observed on day 3 following levobunolol treatment, while apraclonidine induced an increase on day 15. Blood pressure was reduced in all measurement time points following apraclonidine treatment. A negative correlation between QT interval and HR was only observed in dogs treated with timolol. In conclusion, levobunolol was the only drug that induced significant alterations in PS. Apraclonidine was the only drug that induced systemic hypotension. Timolol was the only drug to that induced a negative correlation between QT and HR.